LITERATUR REVIEW : PENGARUH PENGGUNAAN SITZH BATH AIR HANGAT DAN REBUSAN DAUN SIRIH HIJAU TERHADAP PENYEMBUHAN LUKA PERINEUM IBU POSTPARTUM - Elma Destriyani; Febi Ratnasari; H. AYG Wibisono (Yayasan Nusantara Hasana Berdikari, 2023)
Background: Care of the perineum, both during and after delivery, has long been an interesting discussion and is in great demand in the world of health, especially in the field of childbirth. Purpose: this writing is to view and review articles related to the effect of using warm water sitzh baths and decoction of green betel leaves on the healing of perineal wounds in postpartum mothers. The results of knowing the effect of using a sitzh bath of warm water and decoction of green betel leaves on postpartum mother perineal wound healing, the number of articles used were 10 articles which had been published nationally and internationally. Conclusion: From the 10 articles that have been studied, there is a significant positive effect on the use of warm water sitzh bath and green betel leaf decoction on the healing of perineal wounds in postpartum mothers, so perineal wounds in postpartum mothers with the use of warm water sitzh baths have a slower healing time than in a decoction of green betel leaves. Suggestion: For postpartum mothers who have perineal wounds in the healing period, they can use a sitzh bath with warm water or decoction of green betel leaves as an alternative for healing because besides being able to speed up the drying of perineal wounds it can also relieve pain.